Memberdayakan Dosen melalui Kepemimpinan Pelayan: Pengaruh Literasi Digital dan Adaptasi Budaya - Agus Susanto; Elyzabeth Wijaya; Hendry Hendry; Septa Diana Nabella; Yandra Rivaldo (Society, 2024)
This study examines the impact of digital literacy and adaptable culture on lecturer performance, with servant leadership as a mediating variable. The Institute of Information Technology and Business executed the study, with several lecturers participating as responders. Digital literacy is a crucial component in the age of technological transition, whereas adaptable culture signifies an institution’s capacity to adjust to evolving environmental conditions. This study proposes that servant leadership, prioritizing service-oriented leadership, mediates the association among digital literacy, adaptable culture, and lecturer performance. This study uses a validated questionnaire to gather data through a quantitative methodology and survey technique. We employ route analysis methodologies to examine the interrelationships among variables. The study’s outcomes are anticipated to elucidate how digital literacy and adaptable culture might enhance professor performance by reinforcing servant leadership conduct. These findings hold significant implications for formulating higher education policies, particularly in addressing the challenges of the digital age and the intricacies of the professional landscape. This study offers theoretical contributions by enhancing the comprehension of the interplay between digital literacy, corporate culture, and leadership within an academic framework.